SETD2-H3K36ME3: an important bridge between the environment and tumors - He, Jiahui; Xu, Tangpeng; Zhao, Fangrui; Guo, Jin; Hu, Qinyong (Frontiers in Genetics, 2023)
Epigenetic regulation plays an important role in the occurrence, development and treatment of tumors. The histone methyltransferase SETD2 plays a key role in mammalian epigenetic regulation by catalyzing histone methylation and interacting with RNA polymerase II to mediate transcription elongation and mismatch repair. As an important bridge between the environment and tumors, SETD2-H3K36me3 plays an important role in the occurrence and development of tumors. Many tumors, including renal cancer, gastric cancer, lung cancer, are closely related to SETD2 gene mutations. The SETD2-H3K36me3 signaling pathway plays a key part as in common tumor suppressor mechanisms is also an important target for clinical disease diagnosis and treatment. Here, we review the structure and function of the SETD2 gene and how the SETD2-H3K36me3 signaling pathway functions as a bridge between the environment and tumors to provide an in-depth understanding of the role of the SETD2-H3K36me3 signaling pathway in the occurrence and development of various tumors, which is of great significance for future disease diagnosis and treatment.